2010
DOI: 10.1103/physrevb.82.172410
|View full text |Cite
|
Sign up to set email alerts
|

Kondo-like effect in magnetoresistive CuCo alloys

Abstract: Electronic transport properties of twin roller melt spun Cu 100−x Co x ͑x =10,15͒ alloys, are investigated in the temperature range between 10 and 300 K. Negative magnetoresistance is observed up to 0.85 T in the as-cast state, which further increases with a treatment of 1 h at 923 K. Resistance exhibits a metallic behavior below room temperature and draws a minimum near 30 K in all the as-cast microstructures; this minimum diminishes when a magnetic field is applied and completely disappears after high-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The study of granular magnetic systems composed of magnetic nanoparticles embedded in a nonmagnetic metallic matrix has experienced growing interest in the last decade. Their giant magnetoresistance effect (GMR) attracts continuous attention because of potential magnetic recording and magnetic nanosensing applications. , The main generation mechanism of GMR is the spin-dependent scattering of conducting electrons at interfaces between the magnetic particles and the nonmagnetic metallic matrix . Therefore, a detailed description of the interface is necessary to understand the GMR behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The study of granular magnetic systems composed of magnetic nanoparticles embedded in a nonmagnetic metallic matrix has experienced growing interest in the last decade. Their giant magnetoresistance effect (GMR) attracts continuous attention because of potential magnetic recording and magnetic nanosensing applications. , The main generation mechanism of GMR is the spin-dependent scattering of conducting electrons at interfaces between the magnetic particles and the nonmagnetic metallic matrix . Therefore, a detailed description of the interface is necessary to understand the GMR behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Allia et al [14] studied melt-spun CoCu ribbons and showed that the classical superparamagnetic model failed to coherently account for the results of a systematic study of isothermal magnetization curves measured at different temperatures, and the concept of 'interacting superparamagnet' had to be applied. Electro-and magneto-transport properties of Co 0.1 Cu 0.9 and Co 0.15 Cu 0.85 melt-spun ribbons were studied by Fabietti et al [25]. Panissod et al [26] studied granular Co 0.1 Cu 0.9 alloys and analyzed behavior of the thermoremanent magnetization (TRM), which provided relevant information about the distribution of blocking temperatures within the samples [27] clearly revealing the existence of three different phases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depending on composition and thermal treatment, these binary alloys exhibit spin dependent electron transport, evidenced by Kondo-like scattering [6] and giant magnetoresistance (GMR) effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…In previous articles [6,17] we have reported that twin-roller meltspinning techniques are suitable to obtain the desired precipitation substructure directly from the melt, in a single step, just by selecting the adequate casting conditions. In the reported results, casting conditions led to a microstructure in which Co coherent precipitates coexist with segregation strips of about 50 nm wave length, exhibiting MR behavior up to 0.8% at 300 K and 0.85 T. This modulation was attributed to spinodal decomposition, despite the predicted XRD configuration for this case (a central peak and two satellite peaks corresponding to the different compositions) is not observed.…”
Section: Introductionmentioning
confidence: 99%